Jumps and Lower Limb Strength Asymmetry in Young Soccer Players: Differences Between Sand and Conventional Surfaces - Italo Sannicandro; Giacomo Cofano; Rosario D'Onofrio; Andrea Piccinno (OVS LLC, 2023)
Study purpose. The aim of the study was to evaluate jumping performance and lower limbs strength asymmetry in young soccer players by comparing this movement performed on both a conventional surface and a sand surface. Materials and methods. 20 young soccer players under 17 years old randomly performed a standing long jump, a single hop jump in the sagittal plane (Hop Jump Test) and a single side hop jump in the frontal plane (Side Hop Jump Test), first on a conventional surface (natural grass) and then on sand. The jump distance and strength asymmetry was calculated using the formula: (NDL / DL) x 100. Results. The values from the two different jumping conditions showed a statistically significant decrease in the Broad Jump Test (p<0.001, ES: 3.56), Hop Jump Test left limb (p<0.001, ES: 4.99), Hop Jump Test right limb (p<0.001, ES: 3.95), Side Hop Jump Test left limb (p<0.001, ES: 4.67) and Side Hop Jump Test right limb (p<0.001, ES: 2.98) in the sand condition. The asymmetry values in the Hop Jump Test and the Side Hop Jump Test showed a statistically significant increase (+21.5%, p<0.001, ES: 3.66 and +41.1%, p<0.001, ES: 1.99, respectively) when comparing the performance on grass and sand. Conclusions. This different performance response in the two different jumping modes leads to the hypothesis that young soccer players who want to stress their explosive strength ability and joint stability should favor the use of one-leg rather than two-leg jumps. The values described in the study lead to the hypothesis that training on sand should be suggested when the young soccer player presents modest values of inter-limb asymmetry measured on a conventional surface.